Evaluation of Pulmonary Effects of 3-D Printer Emissions From Acrylonitrile Butadiene Styrene Using an Air-Liquid Interface Model of Primary Normal Human-Derived Bronchial Epithelial Cells. (August 2022) - Farcas, Mariana T.; McKinney, Walter; Coyle, Jayme; Orandle, Marlene; Mandler, W. Kyle; Stefaniak, Aleksandr B.; Bowers, Lauren; Battelli, Lori; Richardson, Diana; Hammer, Mary A.; Friend, Sherri A.; Service, Samantha; et al.
This study investigated the inhalation toxicity of the emissions from 3-D printing with acrylonitrile butadiene styrene (ABS) filament using an air-liquid interface (ALI) in vitro model. Primary normal human-derived bronchial epithelial cells (NHBEs) were exposed to ABS filament emissions in an ALI for 4 hours. The mean and mode diameters of ABS emitted particles in the medium were 175 ± 24 and 153 ± 15 nm, respectively. The average particle deposition per surface area of the epithelium was 2.29 × 10 7 ± 1.47 × 10 7 particle/cm 2, equivalent to an estimated average particle mass of 0.144 ± 0.042 μg/cm 2 . Results showed exposure of NHBEs to ABS emissions did not significantly affect epithelium integrity, ciliation, mucus production, nor induce cytotoxicity. At 24 hours after the exposure, significant increases in the pro-inflammatory markers IL-12p70, IL-13, IL-15, IFN-γ, TNF-α, IL-17A, VEGF, MCP-1, and MIP-1α were noted in the basolateral cell culture medium of ABS-exposed cells compared to non-exposed chamber control cells. Results obtained from this study correspond with those from our previous in vivo studies, indicating that the increase in inflammatory mediators occur without associated membrane damage. The combination of the exposure chamber and the ALI-based model is promising for assessing 3-D printer emission-induced toxicity.